Unusual case of cellulitis due to primary cutaneous histoplasmosis - Paul, Vishesh (BMJ Case Rep, 2018)
A 63-year-old white man with a history of rheumatoid arthritis on adalimumab was admitted to the hospital for left arm swelling and erythema. On physical examination, the patient was afebrile and non-toxic appearing and there was tense oedema of the left forearm. Initial laboratory work was unremarkable except for elevated inflammatory markers. MRI of the arm showed non-specific findings of inflammation. The patient was started on empiric antibiotics but did not improve. Given the patient’s immunosuppression, early consideration was given to fungal or mycobacterial causes. Initial serum fungal studies were negative and the patient was taken for diagnostic local incision and biopsy of the left volar forearm. Grocott’s methenamine silver and periodic acid–Schiff staining revealed fungal organisms resembling Histoplasma and intraoperative fungal cultures grew Histoplasma capsulatum confirming the diagnosis. The patient was treated with a 6-month course of itraconazole with improvement in his condition and eventual complete resolution.